Equity-centered community design - Field guide - Creative Reaction Lab (Creative Reaction Lab, 2019)
Equity-Centered Community Design, created by Creative Reaction Lab, is a unique creative problem solving process based on equity, humility-building, integrating history and healing practices, addressing power dynamics, and co-creating with the community. This design process focuses on a community’s culture and needs so that they can gain tools to dismantle systemic oppression and create a future with equity for all. Creative Reaction Lab’s goal is to share equity-centered design to achieve sustained community health, economic opportunities, and social and cultural solidarity for all.
Keywords: Accès gratuit sur inscription; EDI; Planification; États-Unis